Benzenesulfonamides incorporating bulky aromatic/heterocyclic tails with potent carbonic anhydrase inhibitory activity. Issue 24 (15th December 2015) - Bozdag, Murat; Alafeefy, Ahmed M.; Vullo, Daniela; Carta, Fabrizio; Dedeoglu, Nurcan; Al-Tamimi, Abdul-Malek S.; Al-Jaber, Nabila A.; Scozzafava, Andrea; Supuran, Claudiu T.
Graphical abstract: Abstract: Three series of sulfonamides incorporating long, bulky tails were obtained by applying synthetic strategies in which substituted anthranilic acids, quinazolines and aromatic sulfonamides have been used as starting materials. They incorporate long, bulky diamide-, 4-oxoquinazoline-3-yl- or quinazoline-4-yl moieties in their molecules, and were investigated for the inhibition of four physiologically relevant carbonic anhydrase (CA, EC 4.2.1.1) isoforms, the cytosolic human (h) hCA I and II, as well as the transmembrane hCA IX and XII. Most of the new sulfonamides showed excellent inhibitory effects against the four isoforms, with K I s of 7.6–322 nM against hCA I, of 0.06–85.4 nM against hCA II; of 6.7–152 nM against hCA IX and of 0.49–237 nM against hCA XII; respectively. However no relevant isoform-selective behavior has been observed for any of them, although hCA II and XII, isoforms involved in glaucoma-genesis were the most inhibited ones. The structure–activity relationship for inhibiting the four CAs with these derivatives is discussed in detail.